Influence of different burs and acid ultrasonic agitation on the bonding of fiber posts to root dentin - Julio Cezar Chidoski-Filho; Giovana Mongruel Gomes; Bruna Fortes Bittencourt; Alessandra Reis; Osnara Maria Mongruel Gomes; João Carlos Gomes (Universidade Estadual de Campinas, 2018)
Aim: The objective is to evaluate the influence of different burs used to prepare the root canal space and acid ultrasonic agitation on bond strength (BS) between glass fiber posts (GFP) and root dentin. Methods: After endodontic treatment, the root canal spaces of 36 extracted human canines were prepared, according to the rotary instrument used (n=18): carbide bur (CB), provided by the post manufacturer and a diamond bur (DB). In both groups, the fiber posts were cemented with the adhesive system Ambar and resin cement Allcem, following the manufacturer`s instructions. Previously to the cementation procedures, the groups were subdivided into 2 groups (n=9), according to the phosphoric acid application mode: conventional etching (CE) and active etching (AE), performed by ultrasonic tip, both for 15s. Before the cementation procedures and after the acid application, 1 root of each group was randomly selected for ultrastructural morphological evaluation by SEM. After 1 week of the cementation, 8 specimens per group were transversely sectioned into six 1-mm thick slices, the root canal regions (cervical, medium and apical) were identified and the push-out test was performed to evaluate BS. Data were analyzed by 3-way ANOVA and Tukey test (α=0.05). Results: The results showed that the cross-product interaction of all factors was significant (P=0.035). Higher bond strength values were obtained when a DB with conventional etching, instead of CB, was used to prepare the root post space. Conclusion: It may be concluded that the use of diamond burs with conventional etching yields high BS values in all root canal thirds.